Valorización de las empresas: Unión de Cervecerías Peruanas Backus y Johnston, Molson Coors Beverage Co. - Caro Mori, Fiorella del Rocio (2024)
This executive summary provides an overview of the valuation process of two prominent beer companies: Unión de Cervecerías Peruana Backus y Johnston (hereinafter "Backus") and Molson Coors Beverage Co. (hereinafter "Molson Coors"). This study is based on historical financial data collected over a five-year period, from 2018 to 2022, and considers macroeconomic factors and market trends, including the COVID-19 pandemic. During the analysis, the dominance of Backus in the Peruvian beer market and the relevance of Molson in the US market were highlighted, with discounted cash flow being used to value both companies, allowing their growth prospects and future profitability to be evaluated. The results revealed that both Backus and Molson are undervalued in the market, with significant growth potential. Backus's per share value is 37.79 PEN, 64.3% above the market price, while Molson Coors has a per share value of 61.71 USD, 0.3% below the market price. In addition, different capital structure scenarios were analyzed, estimating the optimal one for both companies. For Backus, it was suggested to maintain a debt level of 10.6%, very close to the current 9.9%, which would result in a weighted average cost of capital (hereinafter WACC) of 11.34% and Molson Coors would benefit from a level of debt of 50% and with a WACC of 7.6%. In financial terms, it was observed that both companies present a negative cash conversion cycle, indicating efficient management of collections and payments. In addition, the impacts of different levels of debt on the WACC were evaluated, in order to identify the ideal capital structure for each company. In summary, the acquisition or maintenance of shares of both companies is recommended due to their undervaluation in the market and their growth capacity. However, the importance of prudent management of the capital structure is emphasized to ensure long-term financial sustainability.